Application of da Vinci robot with the"3 + 2" mode in radical gastrectomy for gastric cancer. Issue 46 (13th November 2020) - Hu, Ming; Han, Caiwen; Guo, Tiankang; Tian, Hongwei; Zhan, Weipeng; Yang, Jing; Jing, Wutang; Deng, Yuan; Li, Xiaofei; Ma, Shixun; Cai, Hui; Ma, Yuntao
Abstract : Abstract: The aim of this study is to investigate the feasibility and advantages of the da Vinci robotic system with the "3 + 2" mode (3 robotic arms and 2 assistants) in radical gastrectomy for gastric cancer. The clinical data of 65 patients who underwent da Vinci robotic gastrectomy with the "3 + 2" mode from July 2016 to October 2019 were grouped into an observation group. An additional 65 patients who underwent robotic gastrectomy under the classic mode during the same period were grouped into a control group. The short-term surgical outcomes were compared between 2 different groups. Compared with the control group, the observation group had a significantly shorter operative time (176.18 ± 15.49 vs 203.85 ± 12.77 minutes, P   <  .001) and lower operation costs ($2761.19 ± $191.91 vs $3690.91 ± $162.82; P   <  .001). No statistical differences in other outcomes were observed ( P  > .05). We show that robotic gastrectomy with "3 + 2" mode is a safe and beneficial surgical procedure in new robotic surgery institutions.